2002
DOI: 10.1046/j.1365-2702.2002.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

The practice of community caregivers in a home‐based HIV/AIDS project in South Africa

Abstract: The aim of this study was to describe the practice of community caregivers in a home-based AIDS care project at seven sites in South Africa. The community caregivers felt positive about the contribution they made, but found it difficult to cope with the poverty and complexity of problems they were faced with. They visited each client an average of five times per month, and their care usually involved counselling and informing, symptom control, psychosocial support and welfare assistance. The caregivers worked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 5 publications
2
78
0
1
Order By: Relevance
“…Home-based care aimed to shift burdens of care, particularly terminal care from the formal health system, to semi-formal agents of care in private, nongovernmental organisations and to house holds.With a few notable exceptions (Uys, 2002), the practice of home-based care implied delegating responsibility for death and dying to household members, generally women, who had to manage the difficult and deeply stressful process with little external support (Akintola,2006;Hunter, 2006). Couched in a language of a seamless ''continuum of care '' (WHO, 2002) between health system, community and home, and drawing on ''communitarian'' ideas of reciprocity and caring in African culture, it's more ''profane'' (Marais, 2005) or real role was to legitimate the widespread practice of turning people with end stage AIDS away from overburdened health facilities.…”
Section: Profile Of Lay Health Workers In the South African Health Symentioning
confidence: 99%
See 1 more Smart Citation
“…Home-based care aimed to shift burdens of care, particularly terminal care from the formal health system, to semi-formal agents of care in private, nongovernmental organisations and to house holds.With a few notable exceptions (Uys, 2002), the practice of home-based care implied delegating responsibility for death and dying to household members, generally women, who had to manage the difficult and deeply stressful process with little external support (Akintola,2006;Hunter, 2006). Couched in a language of a seamless ''continuum of care '' (WHO, 2002) between health system, community and home, and drawing on ''communitarian'' ideas of reciprocity and caring in African culture, it's more ''profane'' (Marais, 2005) or real role was to legitimate the widespread practice of turning people with end stage AIDS away from overburdened health facilities.…”
Section: Profile Of Lay Health Workers In the South African Health Symentioning
confidence: 99%
“…If the forms and training of lay workers outlined above have their roots in different ideological traditions and expectations, the practice of lay work tends to be complex, fluid and heterogenous, defying attempts to develop a one-size-fits-all package of services or mode of regulation (Daniels, Van Zyl, Clarke, Dick, & Johansson, 2005;Henderson, 2008;Uys, 2002). This is true in South Africa as much as elsewhere in the world.…”
Section: Policymentioning
confidence: 99%
“…30 Grade 4 (n = 1): weak evidence Using a Likert rating scale of 1 = excellent to 5 = poor, a cross sectional evaluation of 52 patients accessing HIV home care found high patient satisfaction with care (mean score 1.6) and personal control over care (mean score 2.2), and with both communication (84.6% reporting a professional available to talk) and regularity of contact with staff (80.6% satisfied), though perceived health status remained unchanged. 31 Qualitative (n = 6) Qualitative data from patients receiving home based care reported patients particularly valuing information giving, support, welfare assistance, and specialist clinical intervention and referrals (focus group data, number unspecified) 32 as well as enhanced human dignity 33 (patient interviews, number unspecified). Patient interviews in other studies reported less disturbance of daily routine 34 (nine interviews) 35 (five interviews) fewer hospital visits and high satisfaction and quality of care 34 (nine interviews) 36 (265 interviews).…”
Section: Grade 3 (N = 7): Weaker Evidencementioning
confidence: 99%
“…The impact of mortality due to HIV/AIDS has given rise to lower life expectancies, higher death rates, lower population and growth rates and more changes in the distribution of population by age and sex than expected. In sub-Saharan Africa alone, the epidemic has orphaned nearly 12 million children aged less than 18 years (Uys, 2002;UNAIDS, 2008).…”
Section: Introductionmentioning
confidence: 99%